Unveiling safety profile of Pereskia bleo leaf extract: A comprehensive study on female toxicity and teratogenicity in Sprague Dawley rats - Khalaf, Taif Kareem; Nazri, Nor Amalia; Abdulrazak, Mohammed Hussain; Bakar, Ainul Bahiyah Abu; Ezumi, Mohd Fuad Wan; Ismail, Norzila (Journal of Chemical Health Risks, 2024)
Pereskia bleo (P. bleo), renowned for its traditional medicinal use in various countries, is valued for its therapeutic potential. While medicinal plants hold immense promise, concerns regarding potential adverse effects on normal cells and teratogenicity remain. This study evaluated the influence of methanol extract of Pereskia bleo (MEPB) leaves on female toxicity and teratogenicity in Sprague Dawley rats. Female rats (n=40) were divided into four groups receiving MEPB doses (0, 250, 500, and 1000 mg/kg/day) during pre-mating, mating, and gestation periods. Gas Chromatography-Mass Spectrometry (GC-MS) analysis exhibited that MEPB leaves contain phenolic compounds, terpenoids, phytosterols, and fatty acids. Remarkably, all the animals exhibited regular oestrous cycles, maintaining body weight, and showed no signs of toxicity or abnormal behavior. Visceral organ weights and histological analysis revealed no significant alterations, attesting to the extract's safety. Pregnancy outcomes, including corpora lutea, implantation sites, percentages of pre- and post- implantation death, gravid uterine weight, number of live and dead fetuses, fetal body weight, and fetal sex ratio, remained unaffected. Furthermore, meticulous fetal examinations confirmed that MEPB did not impact foetal parameters or induce deformities. Importantly, daily MEPB consumption (250-1000 mg/kg) from pre-pregnancy to pregnancy did not compromise maternal or fetal well-being. These results underscore the lack of embryotoxic or teratogenic effects of MEPB, highlighting its potential for safe therapeutic applications.